Perubahan Mutu Buah Pepaya Varietas IPB 9 (Calina) Selama Penyimpanan Pasca Simulasi Transportasi - Ismaya, Pandu Legawa; Faturochman, Hadi Yusuf; Darmawati, Emmy; Setyadjit, Setyadjit (Faculty of Agricultural Technology, Universitas Semarang, 2023)
Papaya (Carica Papaya L.) IPB 9 (calina) variety is a papaya fruit that has thick, sweet flesh and very high fruit productivity. During the transportation process of papaya, mechanical damage (bruises, abrasions, weight loss) and physiological damage often occur, which can cause papaya decrease in quality during storage before consumption. The purpose of this study was to determine changes in the quality of papaya after 2-hour transportation simulation. The research design used a randomized block design (RAK) with the treatment of the position of the fruit in the packaging, which was stored horizontally (KS1) and vertically (KS2) during the transportation simulation process. Papaya hat has been simulated for transportation is stored at 18–20oC for 12 days. Quality of papaya weight loss stored for 12 days for KS1 reached 7.34% and KS2 reached 7.43%. Hardness quality of papaya stored for 12 days for KS1 is 0.84 kgf, and for KS2, it is 0.76 kgf. Quality of papaya skin color after 12 days of storage decreased the freshness of the papaya fruit, but it was still fit for consumption. Total dissolved solids content after being stored for 12 days for KS1 reached 11.45% and KS2 reached 11.32%.